LECTURERS' PERCEPTION ON THE USE OF WHATSAPP IN TEACHING AND LEARNING ACTIVITIES DURING COVID-19 - sari berlianti (JAMBI-ENGLISH LANGUAGE TEACHING, 2021)
The covid-19 has an impact on the educational field. The learning process has changed from conventional to online learning. Several applications are offered to help educators in doing online learning. One of them is Whatsapp application. Whatsapp is one of the information media that is widely used by many people, including teachers, lecturers, and students. In subsequent developments, Whatsapp application is not only used to communicate and exchange messages, but Whatsapp is also used for educational purposes. The researcher conducted the study of using Whatsapp in teaching and learning activities during Covid-19 at English Education Study Program Jambi University by implemented a qualitative approach with a case study design in gaining the data. Interviews with four English Lecturers were used to obtain data and evidence about how do they perceive the use of Whatsapp in the teaching and learning process during covid-19. The results of data analysis revealed that all of the lecturers have many positive perceptions rather than the negative one about using Whatsapp to do online learning during covid-19. Using Whatsapp in online learning during covid-19 is easy because lecturers can monitor learning at any time, it does not consume a lot of quotas, and many features available on Whatsapp make it easier for lecturers to take the usefulness of these features to carry out online learning activities such as discussion, sharing learning material in various formats, giving assignments, collecting assignments, giving review or feedback and for academic planning and scheduling.